2016
DOI: 10.1073/pnas.1602751113
|View full text |Cite
|
Sign up to set email alerts
|

E4F1-mediated control of pyruvate dehydrogenase activity is essential for skin homeostasis

Abstract: The multifunctional protein E4 transcription factor 1 (E4F1) is an essential regulator of epidermal stem cell (ESC) maintenance. Here, we found that E4F1 transcriptionally regulates a metabolic program involved in pyruvate metabolism that is required to maintain skin homeostasis. E4F1 deficiency in basal keratinocytes resulted in deregulated expression of dihydrolipoamide acetyltransferase (Dlat), a gene encoding the E2 subunit of the mitochondrial pyruvate dehydrogenase (PDH) complex. Accordingly, E4f1 knock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…However, PDH expression was gradually reduced in Chlamydia stimulated ASC -/- DCs. PDH catalyzes the irreversible oxidative decarboxylation of pyruvate to generate Acetyl-CoA, which is then oxidized by the TCA cycle to generate NADH and FADH2, which are used by the mitochondrial electron transport chain and ATP synthase to generate cellular energy [ 54 56 ]. The result suggests that downregulation of PDH in ASC -/- DCs causes a deficit in energy production and fatty acid biosynthesis which impairs DC differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…However, PDH expression was gradually reduced in Chlamydia stimulated ASC -/- DCs. PDH catalyzes the irreversible oxidative decarboxylation of pyruvate to generate Acetyl-CoA, which is then oxidized by the TCA cycle to generate NADH and FADH2, which are used by the mitochondrial electron transport chain and ATP synthase to generate cellular energy [ 54 56 ]. The result suggests that downregulation of PDH in ASC -/- DCs causes a deficit in energy production and fatty acid biosynthesis which impairs DC differentiation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Goguet-Rubio et al revel a central role for DLAT in the pyruvate metabolism program regulated through E4 transcription factor 1 [40]. Lee et al used cDNA microarray analysis to study the placental gene expression related to glucose metabolism and found nine genes with altered expression levels, including DLAT, which related to the tricarboxylic acid cycle pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, E4F1 directly controls the transcription of genes encoding several essential subunits and regulators of the PDC in various cell types, including the E2 and E3 subunits of the PDC core enzyme ( Dlat , Dld ), the mitochondrial pyruvate carrier ( Mpc1/Brp44l ), the mitochondrial transporter of the PDH co-factor Thiamine Pyrophosphate/TPP ( Slc25a19 ), and the regulatory subunit of the PDC phosphatases ( Pdpr ). Consistent with its role in the regulation of the PDC, stable isotope tracing experiments using 13 C-labelled glucose showed that E4f1 inactivation, decreases glucose-derived AcCoA production and enhances lactate production [ 31 , 32 , 33 ]. Perturbation of E4F1 functions in pyruvate metabolism has clinical implications.…”
Section: The P53 Pathway Controls Multiple Metabolic Pathwaysmentioning
confidence: 98%